Study of Utilizations of Recycled LDPE Plastic and Stone Ash Waste from Remaining Split Stone Fragments for Block Paving Application. (September 2020) - Arnandha, Y; Rakhmawati, A; Ali, H H
Abstract: Several waste materials have been continuously investigated for possible use as substitutes for materials in the field of civil engineering; one of them is plastic waste, due to the fact that plastic waste is simultaneously increasing. In this study, the block paving was made from recycled plastic bag (LDPE) with the addition of stone ash from stone crusher process waste for the value of 0%; 2.5%, 5%, 7.5%, and 10%. These additions of stone ash were intended in order to increase water absorption and increase surface roughness. Several physical and mechanical tests were carried out according to SNI-03-0691-1996. From the compressive test, the highest compressive strength is 13.43 MPa. Based on the results of the sodium sulphate resistance test and the external appearance tests, it showed that all block paving was in good condition with solid surface. In accordance toSNI-03-0691-1996, the paving block was included in the class-C quality which can be used for pedestrians.